Pengaruh Pertumbuhan Ekonomi terhadap Emisi Gas Karbon Dioksida (CO2): Data Panel Negara ASEAN Tahun 2000-2019 - Musyarof, Zaky; Qomari, Indira Nur (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2023)
The EKC hypothesis states that there is a link between economic development and environmental degradation. Divided into three phases, the hypothesis states that a country's economic development will increase environmental degradation until at a certain turning point it will decrease environmental degradation. Based on a number of studies, only a handful of countries have been identified as having reached the turning point. Unfortunately, many of these studies focus on Europe and developed countries. While in ASEAN, there are differences in the identification of the relationship between GDP and CO2 emissions. This paper aims to provide a more up-to-date identification of ASEAN's position in the EKC hypothesis, whether the ten ASEAN member countries have reached a turning point in their economic development during the period 2000-2019. The panel data regression analysis method with the random effect model as the best model produced a positive regression coefficient value. Thus, it can be concluded that economic growth in ASEAN goes in the same direction as the growth of CO2 emissions. In other words, the ten countries had not yet reached the turning point in the EKC hypothesis. The results of this study also showed that the efforts that had been taken in the transformation towards a green economy have not yet yielded tangible results. Reflecting on this, stronger commitments must be made and must touch all sectors of the economy.